2011
DOI: 10.1600/036364411x553090
|View full text |Cite
|
Sign up to set email alerts
|

The Peat Moss Sphagnum cuspidatum in Australia: Microsatellites Provide a Global Perspective

Abstract: The distribution of Sphagnum cuspidatum has been subject to controversy. Although historically reported from all continents except Antarctica recent authors consider S. citspidatum to be endemic to Europe and eastern North America. Microsateilites from Australian plants morphologically identified as S. cuspidatum were compared to microsatellites of plants morphologically identified as S. cuspidatum collected from other regions. The species was found to occur in Australia as well as on every continent except An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 24 publications
2
21
0
Order By: Relevance
“…Although macroscopically and microscopically variable, the range of variation among TDF plants fell within that observed in allotriploid S. 6falcatulum on South Island, conforming to morphotypes associated with wetter microhabitats (Karlin et al, 2009(Karlin et al, , 2011b. Although typically branched, simplex morphotypes were present in both regions.…”
Section: Morphologysupporting
confidence: 51%
See 3 more Smart Citations
“…Although macroscopically and microscopically variable, the range of variation among TDF plants fell within that observed in allotriploid S. 6falcatulum on South Island, conforming to morphotypes associated with wetter microhabitats (Karlin et al, 2009(Karlin et al, , 2011b. Although typically branched, simplex morphotypes were present in both regions.…”
Section: Morphologysupporting
confidence: 51%
“…marker 9) when we consider all the alleles amplified per individual at a given microsatellite marker to be a collective unit, and 'locus' when the data are treated as being haploid (Karlin et al, 2009). Karlin et al (2009Karlin et al ( , 2011b found that it was possible to assign alleles at six microsatellite markers to the parental subgenomes (subgenome T and combined subgenomes R/S) in allotriploid S. 6falcatulum, with no genetic overlap (i.e. no shared alleles) between the parental subgenomes at these six markers.…”
Section: Markers Versus Locimentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, a combination of four loci including rbcL and matK allowed a species resolution of only 65% in a set of Chinese Grimmiaceae (Liu et al, 2011). More variable regions of the genome, and nuclear microsatellites in particular, have therefore increasingly been used in moss species-level systematics (e.g., Caruso et al, 2010;Harbaugh et al, 2011;Karlin et al, 2008Karlin et al, , 2011Korpelainen et al, 2008;Peros et al, 2011;Ramaiya et al, 2010).…”
Section: Introductionmentioning
confidence: 99%